2002
DOI: 10.1002/ijc.10625
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin, a naturally occurring polyphenolic antioxidant flavonoid, inhibits azoxymethane‐induced colon carcinogenesis in male F344 rats

Abstract: The modifying effect of dietary administration of the polyphenolic antioxidant flavonoid silymarin, isolated from milk thistle [Silybum marianum (L.) Gaertneri], on AOM-induced colon carcinogenesis was investigated in male F344 rats. In the short-term study, the effects of silymarin on the development of AOM-induced colonic ACF, being putative precursor lesions for colonic adenocarcinoma, were assayed to predict the modifying effects of dietary silymarin on colon tumorigenesis. Also, the activity of detoxifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 33 publications
4
82
0
3
Order By: Relevance
“…In another similar but more detailed study, it was observed that silymarin administration through diet for 4 weeks either during or after carcinogen (Azoxymethane) exposure led to a significant reduction in the frequency of aberrant crypt foci formation. In long term experiment, silymarin significantly reduced the incidence and multiplicity of colonic adenocarcinomas when fed during initiation or post initiation phase of AOM-induced colon carcinogenesis (Kohno et al, 2002). Silymarin exerted these beneficial effects via the reduction of proliferating cell nuclear antigen (PCNA) positive cells and increase in the number of apoptotic cells.…”
Section: Colon Cancermentioning
confidence: 99%
“…In another similar but more detailed study, it was observed that silymarin administration through diet for 4 weeks either during or after carcinogen (Azoxymethane) exposure led to a significant reduction in the frequency of aberrant crypt foci formation. In long term experiment, silymarin significantly reduced the incidence and multiplicity of colonic adenocarcinomas when fed during initiation or post initiation phase of AOM-induced colon carcinogenesis (Kohno et al, 2002). Silymarin exerted these beneficial effects via the reduction of proliferating cell nuclear antigen (PCNA) positive cells and increase in the number of apoptotic cells.…”
Section: Colon Cancermentioning
confidence: 99%
“…A wide range of studies by us and others have shown strong cancer chemopreventive and anticancer efficacy of silibinin (or its crude form known as silymarin) in different animal tumor bioassay systems as well as in cell culture models of epithelial cancers such as skin (Katiyar et al, 1997;Zi et al, 1997;Ahmad et al, 1998;Lahiri-chatterjee et al, 1999), prostate (Zi et al, 1998b;Zi and Agarwal, 1999a;Dhanalakshmi et al, 2002;Singh et al, 2002a), breast (Zi et al, 1998a;Bhatia et al, 1999) and cervical (Bhatia et al, 1999) cancers. With regard to colon cancer, a recent study has shown cancer preventive effect of silymarin against azoxymethane-induced colon carcinogenesis in male F344 rats (Kohno et al, 2002); however, the underlying mechanism of action remains to be elucidated. In the present study, we employed human colon carcinoma HT-29 cells to investigate the anticancer effects of silibinin and associated molecular events.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules are active against tumours, platelet aggregation, viral infection, and allergic or inflammatory responses. Some of them have antioxidant effects (Kim et al, 1998;Jenab et al, 1999;Schmelz et al, 1999;Akao, 2000;Kim et al, 2000;Jeong et al, 2002;Kohno et al, 2002).…”
Section: Introductionmentioning
confidence: 99%